2019
DOI: 10.1002/lary.28475
|View full text |Cite
|
Sign up to set email alerts
|

Intersegmenter Variability in High‐Speed Laryngoscopy‐Based Glottal Area Waveform Measures

Abstract: Objectives/Hypothesis: High-speed videoendoscopy (HSV) has potential to objectively quantify vibratory vocal fold characteristics during phonation. Glottal Analysis Tools (GAT) version 2018, developed in Erlangen, Germany, is software for determining various glottal area waveform (GAW) quantities. Before having GAT analyze HSV videos, segmenters have to define glottis manually across videos in a semiautomatic segmentation protocol. Such interventions are hypothesized to induce variability of subsequent GAW mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…segmenter variability common to glottis segmentation [57], and thus, are performing as good as experts in the field. Our method is also superior to other (fully automatic) glottis segmentation algorithms available [8], [9], [12], as it is validated on a diverse dataset, computationally highly efficient and also highly portable.…”
Section: Discussionmentioning
confidence: 99%
“…segmenter variability common to glottis segmentation [57], and thus, are performing as good as experts in the field. Our method is also superior to other (fully automatic) glottis segmentation algorithms available [8], [9], [12], as it is validated on a diverse dataset, computationally highly efficient and also highly portable.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in an average IoU score of 0.772 indicating a high overlap across experts. As recently shown, glottis segmentation is inherently subjective 58 , although we believe that the three experts providing the ground-truth ensured being as objective as possible.…”
Section: Technical Validationmentioning
confidence: 96%
“…Previous studies have shown that inter-and intra-rater variability in voice research can be a concern [55][56][57][58] . The BAGLS dataset aims to compensate for this by using segmentations that were crosschecked by multiple experts.…”
Section: Videoendoscopy and Glottis Segmentation Several Imaging Tecmentioning
confidence: 99%
See 1 more Smart Citation
“…the glottal midline, is of great importance for an accurate diagnosis. An anatomical derivation is the most appropriate, yet hard to unequivocally define 13,14 and maybe a source for inter-annotator variability 40 . Defining the glottal midline from a simpler representation, i.e.…”
Section: Definition Of Glottal Midlinementioning
confidence: 99%